-6(m)=-6(8+2n)

Simple and best practice solution for -6(m)=-6(8+2n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(m)=-6(8+2n) equation:


Simplifying
-6(m) = -6(8 + 2n)
-6m = (8 * -6 + 2n * -6)
-6m = (-48 + -12n)

Solving
-6m = -48 + -12n

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Divide each side by '-6'.
m = 8 + 2n

Simplifying
m = 8 + 2n

See similar equations:

| x/23=39 | | -8x+5(4x+4)=164 | | Axy=c | | -319=9(1-9p)-4 | | X-d=a | | 3z-2y=12 | | Z+5y=10 | | m/60=26 | | 134=9n+2(4n-1) | | Ln^2=11 | | 2z+y=12 | | 13/17=v/10 | | sen3x=1/2 | | 7x-5(-7x+6)=-240 | | 4x+3y-z=17 | | 6z-2y=8 | | -5(1+9v)=310 | | 10x+30=20x+20 | | 6x^2+35=68 | | 9z-12y=9 | | -504=3(11x+4)+10x | | 3z-4y=3 | | -7(6)(-1)= | | 35k=1925 | | 5x-57-2x=63 | | 4x^2-28-32=0 | | 18d^5+6d^4+9d^3= | | 3+4Inx=5 | | -7n-10=60 | | X+9=90 | | 2x+2y+z=11 | | 1-17x+37x=1 |

Equations solver categories